2020
DOI: 10.1055/a-1136-9890
|View full text |Cite
|
Sign up to set email alerts
|

Nodularity-like appearance in the cardia: novel endoscopic findings for Helicobacter pylori infection

Abstract: Background and study aims Helicobacter pylori-associated nodular gastritis, which is associated with follicular lymphoid hyperplasia, is mainly recognized in the antrum. However, we have also observed nodularity-like appearance in the cardia. This study aimed to investigate the clinical significance of cardiac nodularity-like appearance in H. pylori-associated gastritis. Patients and methods Patients who underwent esophagogastroduodenoscopy and were evaluated for H. pylori infection for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Our previous study showed excellent prediction accuracy of cardiac nodularity due to H. pylori infection, with 0.928 of accuracy, 0.996 of specificity, 0.571 of sensitivity, 0.960 of positive predictive value, and 0.925 of negative predictive value[ 18 ]. In our previous study, we included only the patients who were evaluated for H pylori infection for the first time, and excluded patients with a history of eradication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed excellent prediction accuracy of cardiac nodularity due to H. pylori infection, with 0.928 of accuracy, 0.996 of specificity, 0.571 of sensitivity, 0.960 of positive predictive value, and 0.925 of negative predictive value[ 18 ]. In our previous study, we included only the patients who were evaluated for H pylori infection for the first time, and excluded patients with a history of eradication.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that nodularity could occur in both the antrum and the cardia[ 18 ]. Cardiac nodularity-like appearance is found more frequently than antral nodularity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Endoscopy is essential to diagnose gastritis, evaluate the presence or absence of H. pylori infection, and assess the risk of gastric cancer. [19][20][21] The Kyoto classification of gastritis is an endoscopy-based classification proposed by the Japan Gastroenterological Endoscopy Society in 2013. It was introduced to estimate the risk of H. pylori infection and gastric cancer on endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained biopsy specimens from two sites, the greater curvature of the corpus and the antrum[ 25 ]. One experienced gastrointestinal pathologist diagnosed neutrophil activity score based on the updated Sydney System in hematoxylin and eosin staining.…”
Section: Methodsmentioning
confidence: 99%